Changes to water quality in the water supply network of Zielona Góra = Zmiany parametrów fizyko-chemicznych wody w sieci wodociągowej w Zielonej Górze - Jakubaszek, Anita; Mossetty, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents physiochemical parameter changes in water supply network of Zielona Góra. On the basis of the obtained test results, the impact of prolonged retention of water in the network on its quality was determined, at the measuring points located on the territory of Zielona Góra. It was shown that together with an increase in distance of measuring points from Water Treatment Plant, content of mainly iron, turbidity and colour increased too. In the results analysis, it was determined that retention time and water distribution are the most significant factors in the network contributing to deterioration of water quality at measuring points.
Keywords: water quality; water supply network; secondary contamination of water; water distribution system; jakość wody; sieć wodociągowa; wtórne zanieczyszczenie wody; system dystrybucji wody